Incidence of intraoperative nausea and vomiting during spinal anaesthesia for caesarean section - Magni, Bridget (Department of Anaesthesia, 2016)
The incidence of intraoperative nausea and vomiting during spinal anaesthesia for caesarean section. Background: Nausea and vomiting (IONV) during spinal anaesthesia (SA) for caesarean section (CS) is unpleasant and may interfere with surgery. We studied the incidence of IONV during elective CS, as well as the influence of ethnicity on this outcome. Methods: Two hundred and fifty eight healthy term patients undergoing SA for elective CS were recruited to this prospective observational study conducted at two Cape Town Level 2 hospitals. Standard practice was employed for SA for CS at UCT (University of Cape Town): 2 mL hyperbaric bupivacaine plus 10 μg fentanyl at the L3/4 interspace, and 15 mL/kg cry stalloid co - load. Spinal hypotension was managed with phenylephrine boluses according to a standard protocol. Nausea and/or vomiting were treated by restoration of blood pressure, and metoclopramide. Intraoperative complaints of nausea, and vomiting, were noted. Patients were also interviewed postoperatively as to any experience of intraoperative - or previous history of nausea. Results: Of the 258 patients enrolled in the audit, 112 (43.4%) were non - African and 146 (56.6%) were Black African patients. The overall incidence (95% CI) of nausea was 32% (0.27 - 0.38), with 20% occurring prior to - and 11% after the delivery. The overall incidence of vomiting was 7% (0.05 - 0.11), with 3.2% occurring prior to, and 3.8% after, delivery. The incidence of nausea and/or vomiting was 33% (0.28 - 0.40). Black Africans experienced significantly less nausea than non - African patients (36/145 [24.8%] vs 47/112 [42.0%] respectively, p = 0.004). There was no significant difference in the incidence of vomiting (10/14 5 [6.8%] vs. 8/112 [7.1%] respectively, p = 0.865). The odds of experiencing intraoperative nausea for patients with any blood pressure value <70% of baseline, were 2.46 (95% CI 1.40 - 4.33). Conclusions Though in keeping with international standards, the clinically significant incidence of nausea and/or vomiting of 33% requires adjustments to the management protocol for spinal hypotension. The inclusion of ethnicity as a risk factor for nausea during SA for CS should be considered.